KAJIAN KAPASITAS DAN KEBERLANJUTAN KELEMBAGAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI (PNPM) PERDESAAN DAN PENGELOLAAN KEUANGAN DI UNIT PENGELOLA KECAMATAN (UPK) - Arif Sofianto; Akmal Afif F. Yasin; Hagni Aratri; Carina Phrita Lydiasari; Eko Nugroho; Alfina Handayani; Tri Risandewi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
PNPM Mandiri Perdesaan is Indonesian Governmnet’s Program to decreasing poverty number in rural area based on comunity institutions. The aim of this research is to decribe the capacity and sustainability of PNPM Mandiri Perdesaan institutions. This research is case study and uses qualitative-descriptive by methode which in implemmantation of PNPM Mandiri Pedesaan in Demak and Temanggung Regencie’s, at Central Java Provinces. This research concludes that PNPM Mandiri Pedesaan institutions needs to legality of status, increased system and human ability.